A protein corona study by scattering correlation spectroscopy: a comparative study between spherical and urchin-shaped gold nanoparticles. Issue 8 (11th February 2019) - Moustaoui, Hanane; Saber, Justine; Djeddi, Ines; Liu, Qiqian; Movia, Dania; Prina-Mello, Adriele; Spadavecchia, Jolanda; Lamy de la Chapelle, Marc; Djaker, Nadia
Abstract : Gold nanoparticle interaction with proteins is characterized by using scattering correlation spectroscopy. Protein orientation and binding affinity regarding the nanoparticle surface are discussed. Abstract : The study of protein interactions with gold nanoparticles (GNP) is a key step prior to any biomedical application. These interactions depend on many GNP parameters such as size, surface charge, chemistry, and shape. In this work, we propose to use a sensitive technique named scattering correlation spectroscopy or SCS to study protein interactions with GNP. SCS allowed the investigation of the GNP hydrodynamic radius with a very high sensitivity before and after interaction with proteins. No labeling is needed. As a proof-of-concept, two of the most used morphologies of GNP-based nanovectors have been used within this work: spherical-shaped GNP (GNS) and branched-shaped GNP (GNU). The measurement of several parameters such as the number of proteins binding to one GNP, the binding affinity and the cooperativeness of binding for three different plasma proteins on the GNP surface was carried out. While GNS showed an increase in the hydrodynamic radius, indicating that each kind of protein binds on the GNS in a specific orientation, GNU showed different orientations of proteins due to their multi-oriented surfaces (tips) with a higher surface to volume area. Quantitative data based on the Hill model were extracted to obtain the affinity of the proteins to both GNS and GNU surfaces. Data variations can be understood in terms of the electrostatic properties of the proteins, which interact differently with the negatively charged GNP surfaces.